Developing and implementing teaching in sensitive subject and topic areas : a comprehensive guide for professionals in FE and HE settings - McGovern, William; Gillespie, Aidan; Brandon, Toby; McInnes, Alison (Emerald points., 2024)
Engaging with sensitive topics is crucial for students to develop classroom and workplace resilience. These should be taught in a way that supports the acquisition of new knowledge, skills, and attributes, and that enables students to prepare for and thrive in their future professional life. Providing educators with a comprehensive understanding of the issues involved in teaching sensitive subjects and topics, this collected work invites them to consider their position and practice in the classroom, as well as the implications that this might for the learner and their learning experience. Presenting illustrative examples from the fields of public health, social care, psychology, social work, education, and criminology, contributors draw on the work of active academics and empirical researchers with extensive experience developing and designing relevant teaching activities. Recognising the range of sensitive concerns that staff may need to handle, chapters provide theoretical and practical guidance across a range of subjects, including cultural sensitivity, colonialism, faith and religion, homelessness, care experience, poverty, mental health, trauma, violence, and substance use. Rooted in actual practice, Developing and Implementing Teaching in Sensitive Subject and Topic Areas identifies the best methodology for creating learning environments that feel both safe and critically stimulating for all involved.